A morte do Rio Doce: um estudo sobre os impactos do “desastre da Samarco” na vida dos pescadores e moradores do município de Tumiritinga/MG - Ibrahin, Fabiane Regina Carvalho de Andrade (2021)
In the afternoon of November 5th of 2015, the rupture of Fundão dam happened - a mining tailings dam controlled by Mineradora Samarco Mineração S.A., located near the municipality of Mariana/MG, the Doce River basin -, releasing an estimated volume of 50 million cubic meters (m3) of mud. Resulting countless homeless people, nineteen deaths and an increase the water turbidity of the Doce River along its entire length, generating an impact on water supply Minas Gerais and Espírito Santo cities. The mud wave directly affected the riverside populations of farmers, fishermen and indigenous, covering, directly and indirectly, more than two hundred counties. Taking into account the difficulty of measuring such impacts along the entire length of the Doce River, it was delimited, for the accomplishment of this doctoral research, the municipality of Tumiritinga/MG, with its residents and fishing community that was violently affected by the disaster. Thus, the present thesis proposes to exhibit a study of disaster impacts that occurred the Fundão dam, life, daily habits, cultural and labor practices of the Tumiritinga/MG residents and the fishing community resident the county, addition to a reflective analysis about what really happened that day, with the collapse of the Fundão dam, in order to demonstrate that what happened was an environmental crime